2011
DOI: 10.1177/0956797611418837
|View full text |Cite
|
Sign up to set email alerts
|

Big Time Is Not Always Long

Abstract: To reproduce the duration of an event precisely, one needs to represent the temporal information without being influenced by other magnitude attributes (e.g., size) of the event. In the present study, however, task-irrelevant numerical magnitude automatically affected participants' reproduction of the duration of a stimulus. In Experiment 1, participants made key-press responses to reproduce the duration of numbers. Reproduced durations were shorter for small numbers (e.g., 1) than for large numbers (e.g., 9).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 39 publications
4
48
4
Order By: Relevance
“…Perhaps of greater interest is that this bias has also been demonstrated for symbolic magnitude. For example, the perceived durations of relatively small numbers (e.g., 1, 2) tend to be underestimated, while large numbers (e.g., 8, 9) are overestimated (Chang, Tzeng, Hung, & Wu, 2011;Kiesel & Vierck, 2009;Oliveri et al, 2008;Vicario, 2011;Vicario et al, 2008;Xuan, Chen, He, & Zhang, 2009;Xuan, Zhang, He & Chen, 2007). This finding implies that time-magnitude biases are not purely sensory in nature, but emerge at a semantic level of analysis.…”
Section: Introductionmentioning
confidence: 69%
“…Perhaps of greater interest is that this bias has also been demonstrated for symbolic magnitude. For example, the perceived durations of relatively small numbers (e.g., 1, 2) tend to be underestimated, while large numbers (e.g., 8, 9) are overestimated (Chang, Tzeng, Hung, & Wu, 2011;Kiesel & Vierck, 2009;Oliveri et al, 2008;Vicario, 2011;Vicario et al, 2008;Xuan, Chen, He, & Zhang, 2009;Xuan, Zhang, He & Chen, 2007). This finding implies that time-magnitude biases are not purely sensory in nature, but emerge at a semantic level of analysis.…”
Section: Introductionmentioning
confidence: 69%
“…Another line of evidence for a shared magnitude system has been provided by experimental studies examining the interaction between magnitudes. A number of studies demonstrate bidirectional influence between space and number, (see Bueti and Walsh, 2009; see also Chang et al, 2011). Similar influence has been found between number and time, but with time processing more often affected by number processing than vice versa (e.g., Cappelletti et al, 2011).…”
Section: Core Hypotheses Regarding Ddmentioning
confidence: 99%
“…For example, in a temporal discrimination task, numerical magnitudes can be activated automatically—leading to a subjective time expansion for stimuli with a large number (e.g., 9) and a time compression for stimuli with a small number (e.g., 1), even though the magnitude information was task-irrelevant (Xuan et al, 2007; Oliveri et al, 2008; Vicario et al, 2008). This phenomenon, known as number-time association (NTA) (Bi et al, 2014), has also been found in time reproduction tasks (Chang et al, 2011; Cai and Wang, 2014). …”
Section: Introductionmentioning
confidence: 80%
“…By using a temporal reproduction task with a key-press response, Chang et al (2011) found a typical NTA pattern when the perceptual/concurrent digits appeared during the standard intervals, but an opposite NTA pattern when the digits appeared during the reproductions, implying a time encoding account for the NTA. Recently, the time encoding account for the NTA has been challenged by an alternative explanation, i.e., a time memory-based account for the NTA.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation